Exploring the Challenges of Afghan Refugee Women Facing COVID-19: A Qualitative Study in Iran - Yoosefi Lebni, Javad; Enayat, Halime; Irandoost, Seyed Fahim; Dehghan, Ali Akbar (Frontiers in Public Health, 2022)
Objective: Afghan refugee women in Iran confront many problems in dealing with COVID-19 due to their fragile conditions. Therefore, the aim of this study was to explain the challenges of Afghan refugee women in the face of COVID-19 in Iran with a qualitative approach. Methods: The present study was conducted with a qualitative approach among Afghan refugee women in Iran. Data were collected through semi-structured face-to-face and telephone interviews and were saturated with 30 women. Both targeted and snowball sampling were used. Data were analyzed using conventional qualitative content analysis and Graneheim and Lundman method. Guba and Lincoln criteria were observed to evaluate the quality of research results. Results: 143 primary codes, 12 subcategories and 5 main categories were obtained from data analysis. The main categories include little knowledge and information (limited access to information resources, incomplete knowledge about COVID-19), family problems (intensified experience of violence and conflict in the family, problems related to childbirth and pregnancy), socio-economic problems (exacerbation of economic problems, high-risk living conditions, social isolation, limited support of social and health organizations), health problems (problems related to treatment, injustice in providing services and facilities) and problems after the death of a COVID-19 patient (burial challenges for immigrants; lack of funeral rites). Conclusion: Afghan refugee women in Iran are very vulnerable facing COVID-19 due to their fragile conditions. Social and health institutions and organizations need to provide more support to these women so that they can protect their health and that of their families against COVID-19 and the damage caused by it.